Implementation of Demonstration Method to Improve Students' Understanding of Ablution Practices at SD Negeri 102092 Sibulan - Harahap, Maya Sriyanti; Sarti; Nuruddin, Ahmad; Purba, Yusnar (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the understanding of fourth grade students of SDN 102092 Sibulan, Tebing Syahbandar District, Serdang Bedagai Regency about ablution practices through demonstration methods. The problem faced is the lack of students' understanding of the correct sequence and procedures for ablution. Based on the results of initial observations, most students only know the theory of ablution without being able to practice it properly. This causes many students to make mistakes when performing ablution, such as not washing body parts in sequence or not paying attention to the pillars of ablution properly. Data were collected through observation, interviews, and practical assessments. Observation sheets were used to record student activities during learning, while interviews were used to determine students' understanding before and after learning. In addition to increasing understanding, the demonstration method also had a positive effect on students' attitudes in maintaining cleanliness and discipline. Students were more active, confident, and enthusiastic in practicing ablution because they gained direct experience. Teachers provided individual guidance to students who were still experiencing difficulties, so that each student got optimal learning opportunities. The interaction between teachers and students became more intensive, making learning more meaningful and effective. Thus, the demonstration method has proven to be effective in increasing students' understanding of ablution practices and forming positive habits in daily life.